Influence of Body Mass Index on Balance in Healthy Young Adults - Chanpura, Dhwani; Chang, Naongmuong A. (Advancement and New Understanding in Medical Science Vol. 1, 2024)
Balance is the capacity to maintain a stable base of support with minimum movement. The balance in the human body is frequently classified as static and dynamic. One of the major influencing factors for maintaining balance in normal healthy individuals is body mass index (BMI). A total of 127 participants, 105 females and 22 males between the age group 18 to 29 years volunteered for study. In the study Normal BMI Group comprises of 70 participants Whereas, Overweight BMI Group consisted of 57 participants. when static balance was compared between subjects with normal and overweight BMIs, the findings revealed a significant difference.